Paradigmas en la construcción de software - Bolaños Castro, Sandro Javier (Ingeniería, 2000)
The reality modeling has been one of the task that since the beginning of mankind has been made. Thepaintings discovered in caves are the expression of what man felt and saw around him. Sometime after that, we still continue asking ourselves about our reality and how to represent it in such away that we could master it. This is just the proposal that follows the paradigm, to structure a set of mechanims that allow,in a formal way, to organize the reality wich wecould make decisions about. This article presents the most important points of view, about how reality, can be seen and modeled towards the software construction.